2019
DOI: 10.3390/su11092455
|View full text |Cite
|
Sign up to set email alerts
|

The Penetration of Green Innovation on Firm Performance: Effects of Absorptive Capacity and Managerial Environmental Concern

Abstract: Under the background of environmental sustainability, it is of great significance to investigate how green innovation influences firm performance dimensions in emerging economies. Explicitly, the interaction effects of absorptive capacity (AC) and managerial environmental concern (MEC) on the correlation between green innovation and firm performance dimensions must be explored. Our data were obtained through a questionnaire survey from 253 companies operating in China. Using hierarchical linear modeling (HLM),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
133
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(146 citation statements)
references
References 92 publications
8
133
0
5
Order By: Relevance
“…According to Porter's theory of competitive advantage, if a company implements green technological innovation, it is expected to include increased product competitiveness, reduced production costs, and improved corporate image [33]. To reduce the model analysis, referring to the common methods of economic models, benefits such as competitiveness and corporate image can be quantified as a reduction in production costs [43].…”
Section: Impetus For Green Technological Innovationmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Porter's theory of competitive advantage, if a company implements green technological innovation, it is expected to include increased product competitiveness, reduced production costs, and improved corporate image [33]. To reduce the model analysis, referring to the common methods of economic models, benefits such as competitiveness and corporate image can be quantified as a reduction in production costs [43].…”
Section: Impetus For Green Technological Innovationmentioning
confidence: 99%
“…These benefits can enhance the competitive advantage of firms. Green technological innovation can also create obstacles for competitors [23], and the "isolation mechanism" created by green technological innovation can preserve profit margins and allow firms to gain [32,33]. Benefiting from the cost reduction and revenue increase contributed by green technological innovation, firms can become more competitive [34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Manufacturers thus face the trade-off between costs and benefits when deciding their green innovation mode. Although research has shown that green innovations are positively related to corporate competitiveness and performance [14], many manufacturers still hesitate to develop or adopt radical green innovations due to the associated high R&D spending and production costs, which they believe will weaken their competitiveness [15].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, as most previous studies have suggested (e.g., Cupertino et al [96]; Masocha [97]; Xue et al [98]) the sustainability issues such as environmental, social, and governance standards, may enhance an organization's innovation and long-term growth with a positive effect on its long-term value. The next section adds to this literature by incorporating a model (i.e., throughput model) that examines sustainability issues via a process apparatus as opposed to a black box.…”
Section: Summary For Sustainability Researchmentioning
confidence: 80%